2023
DOI: 10.1186/s40621-023-00434-9
|View full text |Cite
|
Sign up to set email alerts
|

Child injuries in Lebanon: assessing mothers’ injury prevention knowledge attitude and practices

Abstract: Background Childhood injury is a neglected public health problem with a sizeable burden on children’s well-being and their families. This study aims to describe the pattern and types of childhood injuries and to determine the level of mothers’ Knowledge, Attitude, and Practices (KAP) towards childhood injury prevention in Lebanon. The study further examines the association between childhood injury occurrence and mothers’ supervision. Methods This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Only 5.6% of the participants of a study conducted in Saudi Arabia [6] achieved a passing score, which was 12 correct answers out of 14 questions, and 58.2% of mothers had fair knowledge about first-aid in another study, also conducted in Saudi Arabia [7]. Similar results were also found in Lebanon, where a study revealed that 57.4% of participating mothers showed fair knowledge of child injury prevention [8]. The factors associated with mothers' knowledge of first-aid practices regarding domestic accidents were the graduate level of education, having received formal first-aid training courses, and having previous experience of a child injury in the study conducted by Harere et al in Saudi Arabia [6].…”
Section: Introductionmentioning
confidence: 66%
“…Only 5.6% of the participants of a study conducted in Saudi Arabia [6] achieved a passing score, which was 12 correct answers out of 14 questions, and 58.2% of mothers had fair knowledge about first-aid in another study, also conducted in Saudi Arabia [7]. Similar results were also found in Lebanon, where a study revealed that 57.4% of participating mothers showed fair knowledge of child injury prevention [8]. The factors associated with mothers' knowledge of first-aid practices regarding domestic accidents were the graduate level of education, having received formal first-aid training courses, and having previous experience of a child injury in the study conducted by Harere et al in Saudi Arabia [6].…”
Section: Introductionmentioning
confidence: 66%